Penerapan Terapi Kelompok Teknik Self disclosure untuk Meningkatkan Penyesuaian Diri Anak Jalanan Di Panti Sosial - Riani, Widia Sesha; Putri, Roza Elmanika; Sovitriana, Rilla (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
The Bina Insan Bangun Daya 2 Jakarta Social Institution is a social institution that provides temporary shelter for people with Social Welfare Problems (PMKS) as a result of policing and social outreach and has the responsibility to provide motivation and social guidance for PMKS who will be referred to related social institutions in accordance with the problem, either being returned to the family or sent back to the place of origin. One of the PMKS in the community is street children; they are given guidance and provided with services and rehabilitation so that they can adjust to the community environment and have the ability to start new businesses and no longer associate illegally and work on the streets; it’s just that street children who are in Social Institutions. After carrying out a psychological examination with clinical interviews, observation, psychological tests, and self-adjustment scales, it is known that WBS are less able to adapt, which is marked by being lazy to follow various guidance and skills training, preferring to be alone, being unable to accept oneself, and being lazy to get along. After doing group therapy with self-disclosure techniques, street children begin to want to participate in activities, are calm and optimistic, and are able to socialise. The percentage increase in self-esteem averaged 27.9%.